Ultrasonic P- and S-Wave Reflection and CPT Soundings for Measuring Shear Strength in Soil Stabilized by Deep Lime/Cement Columns in Stockholm Norvik Port - LINDH, Per; LEMENKOVA, Polina (Archives of Acoustics, 2023)
In this research project, the measurements of the ultrasonic P- and S-waves and seismic cone penetration testing (CPT) were applied to identify subsurface conditions and properties of clayey soil stabilized with lime/cement columns in the Stockholm Norvik Port, Sweden. Applied geophysical methods enabled to identify a connection between the resistance of soil and strength in the stabilized columns. The records of the seismic tests were obtained in the laboratory of Swedish Geotechnical Institute (SGI) through estimated P- and S-wave velocities using techniques of resonance frequency measurement of the stabilized specimens. The CPT profiles were used to evaluate the quality of the lime/cement columns of the reinforced soil by the interpretation of signals. The relationship between the P- and S-waves demonstrated a gain in strength during soil hardening. The quality of soil was evaluated by seismic measurements with aim to achieve sufficient strength of foundations prior to the construction of the infrastructure objects and industrial works. Seismic CPT is an effective method essential to evaluate the correct placement of the CPT inside the column. This work demonstrated the alternative seismic methods supporting the up-hole technology of drilling techniques for practical purpose in civil engineering and geotechnical works.